Rancang Bangun Aplikasi Berbasis Android Untuk Mempermudah Akses Pelayanan Surat Dan Informasi Kegiatan Masyarakat (Studi Kasus : Perumahan Bumiasri Kelurahan Kutabumi) - Suryana, Dimas Rizqi; Ramadhan, Ikhsan (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
An Android-based application has been designed to enhance efficiency in disseminatingcommunity activity information and managing correspondence services in Bumiasri ResidentialArea, Kutabumi Village. This application facilitates residents in accessing information in real-time,reduces reliance on manual methods, and increases community participation. The implementationof technologies such as Flutter and Dart enables flexibility and compatibility with various devices,while the use of Strapi as a CMS simplifies content and data management within the application.This application is expected to provide an effective solution to meet the information and serviceneeds of the community in the residential environment.